PENGARUH MOTIVASI DAN SIKAP PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN ULANG - Laily, Elly Nur; Nasution, Ute Chairuz; Tjahjono, Endro (Jurnal Dinamika Administrasi Bisnis, 2018)
This research entitled "The Influence of Motivation and Customer Attitudes toward Purchase Decision (Case Study On My Self-service Reny in Surabaya)". This study aims to determine the influence of customer motivation and attitudes toward the re-purchase decision at Reny self-service Surabaya. The population in this study are consumers who shop at Reny Swalayan-ku Surabaya minimum age 18 years and who has made a minimum purchase twice in Reny Swalayan-ku Surabaya and samples taken as many as 100 respondents. Variables used are motivation, customer attitude and purchasing decision.Method of data collection using questionnaire method by using technique of Non Probability Sampling that is accidental sampling. The data obtained were analyzed using multiple linear regression analysis which was processed with the help of SPSS program application.The results obtained conclusion as follows:1. There is an individual influence of motivation to the repurchase decision and the customer's attitude toward the repeat purchase decision is proven and accepted reality of partial test result (t) obtained with significant level <0,05.2. There is mutual influence of customer's motivation and attitudes toward the repeat purchase decision proven and accepted reality of partial test result (F) obtained with significant level <0,000.3. Variable of motivation and attitude of customer have strong relation to repurchase decision equal to 6,44% and besides that independent variable have contribution equal to 65,1% to dependent variable and the rest 34,9% influenced by other variable.Keywords: Motivation, Customer Attitude and Purchase Decision